Phosphate and vascular calcification: Emerging role of the sodium-dependent phosphate co-transporter PiT-1 - Lau, Wei Ling; Festing, Maria H.; Giachelli, Cecilia M. (Thrombosis and Haemostasis, 2010)
Elevated serum phosphate is a risk factor for vascular calcification and cardiovascular events in kidney disease as well as in the general population. Elevated phosphate levels drive vascular calcification, in part, by regulating vascular smooth muscle cell (VSMC) gene expression, function, and fate. The type III sodium-dependent phosphate co-transporter, PiT-1, is necessary for phosphate-induced VSMC osteochondrogenic phenotype change and calcification, and has recently been shown to have unexpected functions in cell proliferation and embryonic development.
Keywords: Phosphate; vascular calcification; PiT-1; kidney disease